The Influence Of Product, Service Quality And Location On Purchasing Decisions For Wardah Products At Batara Pontianak Cosmetic Shop - Muhammad Reinaldi; Haji Helaman Fachri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of product, service quality, and location on purchasing decisions for Wardah products at Batara Pontianak Cosmetic Shop. The background of this research is based on the high competition in the cosmetics business in Pontianak City and Kubu Raya Regency, as well as the importance of product, service, and location factors in influencing consumer decisions. This research uses a quantitative approach with associative methods. Primary data was obtained through a questionnaire distributed to 100 respondents who were consumers of Batara Cosmetic Shop. The data analysis technique uses multiple linear regression analysis with the help of SPSS software. The results showed that simultaneously the variables of product, service quality, and location had a significant effect on purchasing decisions. Partially, the product and location variables have a significant influence on purchasing decisions, while service quality has no significant effect. The coefficient of determination of 76.3% indicates that the independent variables in this study are able to explain the dependent variable strongly. These findings provide implications for store managers to continue to increase product availability and maintain a strategic location in order to increase consumer purchasing power.